Optimization and biological validation of an in vitro assay using the transfected Dm28c/pLacZ Trypanosoma cruzi strain - Gulin, Julián Ernesto Nicolás (2021)
Fil: Fil: Gulin, Julián Ernesto Nicolás. Instituto Multidisciplinario de Investigaciones en Patologías Pediátricas (IMIPP-CONICET); Argentina.